Planning for Climate Adaptation: Evaluating the Changing Patterns of Social Vulnerability and Adaptation Challenges in Three Coastal Cities. (September 2016) - Kashem, Shakil Bin; Wilson, Bev; Van Zandt, Shannon
While recent research has recognized the importance of considering social vulnerability, the changing patterns of social vulnerability within cities and the climate adaptation challenges these shifts pose have yet to receive much attention. In this article, we evaluate the changing patterns of social vulnerability in three coastal cities (Houston, New Orleans, and Tampa) over a thirty-year time period (1980–2010) and integrate neighborhood change theories with theories of social vulnerability to explain those patterns. Through this analysis, we highlight emerging dimensions of vulnerability that warrant attention in the future adaptation efforts of these cities.